O brincar e habilidades sociais de uma criança cega e seus pares videntes na pré-escola - Silva, Carolina Biondo da (2015)
The visual impairment reduces the opportunities in learning and could negatively influence the interaction among peers and the social development of children with this visual limitation. Some behavior singularities are presented among visual impairments children, such as high levels of dependence and bonds with adults, difficult for socializing with other children, especially when they are not stimulated accordingly. Thus, considering the effects of visual impairment and the common difficulties in social development of blind children, in the Early Childhood Education environment, this project aimed to: (a) characterize the playing behavior of a blind child with their sighted peers in recreational activities; (b) identify the social status of the blind child as well as the selected sighted children; (c) evaluate social skills, behavior problems and academic competence of blind child and their sighted peers, according to the teacher. One blind child, 5 years old, enrolled an early childhood local school , and two sighted colleagues, a boy and a girl, both 5 years old, attended to the same class participated in this study. The data collection took place in a town in the countryside of São Paulo state. Each child was filmed in six different sessions in a playful enviroment lasting 15 minutes the session, total 90 minutes each children. Additionally, we applied a sociogram with the students. Their teacher, also answered the SSRS-BR (Social Skills Rating System) that evaluated the social skills of the children according to the teacher‟s opinion. We found resemblances among the three children, considering the act of playing, for them playing with other children and toys demanded the longest period of time. The behavior of handling toys was the second most present behavior. The blind child, in comparison with the sighted children, spent more time playing with toys and other children, besides presenting some common behaviors of people with visual impairment. The sociogram result shows the popular status for the two girls; the sighted boy was classified controversial. According to the data of SSRS-BR, the blind child and the sighted boy were considered with a good repertory of social skills and the sighted girl got a highly elaborated repertory of social skills. The results, on the whole, pointed important aspects between the behaviors of playing of blind child and their sighted peers in preschool, showing that the blind child is socially competent in her social interactions during the play.